2019
DOI: 10.1007/s11199-019-01023-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gender in Worry and Efforts to Cope during Stressful Waiting Periods

Abstract: Waiting for personally significant news is a near-universal experience, but people differ in how they cope with these acute moments of uncertainty. The present study examined whether selfidentified men and women differ reliably in how they experience and cope with uncertain waiting periods, given societal pressures toward (for men) or against (for women) emotional experiences that may be relevant in these moments. Across 20 U.S. studies in field and laboratory settings (total n = 4,714), we examined gender dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…Regarding gender, women showed higher worry than men. These results were consistent with prior research that women were more prone to experience and express fear-based emotions, such as worry (Moccia et al, 2020;Sweeny et al, 2019). However, both the associations between age and gender with worry were trivial.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding gender, women showed higher worry than men. These results were consistent with prior research that women were more prone to experience and express fear-based emotions, such as worry (Moccia et al, 2020;Sweeny et al, 2019). However, both the associations between age and gender with worry were trivial.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, in reference to the association between worry and gender, Gould and Edelstein (2010) demonstrated that young women were more often worried compared to young men due to having less control over the external signs of emotion (Gould & Edelstein, 2010). Accordingly, Sweeny, Kwan, and Falkenstein (2019) highlighted that women both experience and express fear-based emotions (such as worry) more than men do (Sweeny, Kwan, & Falkenstein, 2019). Moccia et al (2020) evidenced that female gender was a relevant biological factor of vulnerability to psychosocial distress due to genetic, hormonal, and socio-cultural aspects (Moccia et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have also shown that girls report higher levels of anxiety than boys during adolescence (Beesdo-Baum & Knappe, 2012 ; McCauley et al, 2017 ; McLaughlin & King, 2015 ; Stapinski et al, 2015 ) and that they are more likely than boys to be diagnosed with anxiety disorders (McCauley et al, 2017 ). Similarly, some studies show that girls report higher levels of worry than boys during adolescence (Muris et al, 2004 ; Sweeny et al, 2019 ), suggesting that this form of RNT might also be accounting for gender differences in anxiety problems during adolescence.…”
Section: Rnt Processes As Mechanisms Of Gender Differences In Depress...mentioning
confidence: 96%
“…As for sex differences, there was a slightly higher number of women in Cluster 3, the segment of "Concerned Seniors." The sex differences such as increased worry among women and different behavior patterns were, however, not significantly reported in the past [39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 78%
“…In their studies on aging and development, Basevitz et al [36] and Wilson et al [37] suggested that with increasing age, older individuals exhibit a lower propensity to worry. Finally, different travel behaviors and levels of satisfaction have been reported between genders [38][39][40] and during times of distress [41][42][43], which is also a point of interest in this study.…”
Section: Travel Worry and Travel Fearmentioning
confidence: 90%